2019
DOI: 10.3390/app9061153
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Modeling of Pressure Swing Adsorption (PSA) Oxygen Generation with Radial-Flow Adsorber

Abstract: Radial flow is an important type of flow direction for large-scale pressure swing adsorption (PSA) oxygen generation systems. In this study, a numerical simulation of a PSA oxygen generation process based on radial-flow adsorbers was performed with two-dimensional CFD modeling. The gas distribution, the maldistribution factor and the pressure difference were comparatively investigated at each flow type of the radial-flow adsorber. Considering the gas adsorption performance, the results indicated that the centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Governing equations: the equation used in this simulation are from literature by Yang et al [18], Wang et al [16] and Chang et al [10]. The describing the overall PSA operations are followed as below.…”
Section: Ideal Gas Law Is Appliedmentioning
confidence: 99%
“…Governing equations: the equation used in this simulation are from literature by Yang et al [18], Wang et al [16] and Chang et al [10]. The describing the overall PSA operations are followed as below.…”
Section: Ideal Gas Law Is Appliedmentioning
confidence: 99%
“…Since the gas velocity through the adsorption unit is driven by pressure drop, a possibility to increase the gas velocity is to distribute the adsorbent in a shorter and thicker column [44]. If the column length is decreased by half and the radius of the column is increased by a factor of √ 2 , the gas velocity can be increased from 0.23 m/s to 0.34 m/s.…”
Section: Second Example: Peak Shaving Of Water In Bathroomsmentioning
confidence: 99%
“…Hamedi et al [17] found a novel radical flow reactor with lower pressure drop, and compared the optimized reactor with an optimized conventional axial flow reactor to ascertain the superiority of the proposed reactor configuration. Yang et al [18] performed a numerical simulation of a PSA oxygen production process based on radial-flow adsorber and found that the centripetal π-flow radial adsorber has the best flow characteristics for the PSA process.…”
Section: Introductionmentioning
confidence: 99%